Preparation method and application of texture ceramic / nano-silver particle composite laminated piezoelectric actuator

By using textured ceramic/nano-silver particles composite laminate structure and template directional growth technology in lead-free piezoelectric ceramic materials, the problem of poor piezoelectric performance of lead-free piezoelectric ceramic materials is solved, and piezoelectric performance with high strain and low strain hysteresis is achieved, which is suitable for a variety of piezoelectric applications.

CN119604180APending Publication Date: 2025-03-11HUANGSHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311742854.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing lead-free piezoelectric ceramic materials have poor piezoelectric properties, large strain hysteresis, and cannot compare with lead-based piezoelectric ceramics, which cannot meet practical application requirements.

Method used

The preparation method of textured ceramic/nanosilver particles composite laminated piezoelectric actuator is adopted to prepare highly oriented ceramic grains through template directional growth technology, and dopant modified nanosilver particles to improve electron mobility, and use a stacked structure to reduce the driving voltage and increase displacement.

Benefits of technology

It significantly improves the piezoelectric performance and obtains a strain loop with high strain and low strain hysteresis. Under an electric field of 30kV/cm, the displacement output reaches 0.65%, which is suitable for piezoelectric micro-displacement actuators and sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604180A_ABST
    Figure CN119604180A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a textured ceramic / nano-silver particle composite laminated piezoelectric actuator, and belongs to the technical field of piezoelectric ceramics. The preparation method comprises the following steps: firstly, preparing a [001] c oriented barium titanate seed crystal template, and preparing lead-free 1-x (B < 0.5 > Na < 0.5 >) T O < 3-x > Ca (A < l > < 0.5 > Nb < 0.5 >) O < 3 > texture ceramic oriented along the [001] c height by adopting a template oriented growth technology; then preparing modified nano-silver particles; and finally preparing the textured ceramic / nano-silver particle composite laminated piezoelectric actuator through a casting film preparation method. The piezoelectric actuator can be widely applied to piezoelectric power generation materials such as a piezoelectric micro-displacement actuator and a piezoelectric sensor which are stable in piezoelectric performance, high in sensitivity and high in accuracy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of piezoelectric ceramics, and in particular relates to a preparation method and application of a textured ceramic / nano-silver particle composite laminated piezoelectric actuator. Background Art

[0002] Piezoelectric ceramics are widely used in brakes, micro-displacement actuators, and sensitive materials. At present, the piezoelectric material that dominates the piezoelectric ceramic market is lead zirconate titanate ceramics. However, lead-based ceramics have serious environmental pollution problems, and lead-free piezoelectric ceramics have become the research focus of many researchers. Among them, barium titanate-based piezoelectric ceramics are considered to be one of the more attractive lead-free piezoelectric ceramic systems.

[0003] Sodium bismuth titanate-based lead-free piezoelectric ceramics have large electro-induced strain, but the non-oriented piezoelectric ceramics prepared by the traditional solid-phase reaction method have large strain hysteresis (>20%), and the performance is still not comparable to that of lead-based piezoelectric ceramics, and cannot meet the requirements of practical applications. Therefore, it is necessary to modify and optimize sodium bismuth titanate-based lead-free piezoelectric ceramics to make them more valuable for application in real life. In recent years, there have been reports of using a multilayer piezoelectric ceramic preparation method to reduce the driving voltage and increase the displacement [Chen, J., Z.-Z. Du, Y.-T. Yang and H. Hu (2021). Ceramics International 47 (11): 15195-15201] However, its piezoelectric material is prepared by the traditional non-oriented sintering method, and the improvement of piezoelectric performance is limited. The template texture technology is used to prepare (Bi 0.5 Na 0.5 )TiO3-Ca(Al 0.5 Nb 0.5 )O3 lead-free piezoelectric ceramic / nanosilver particle composite multilayer actuator has not been reported. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a textured ceramic / nanosilver particle composite laminated piezoelectric actuator to solve the problem of poor piezoelectric performance of piezoelectric materials in the prior art.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator comprises the following steps:

[0007] S1.1-x(Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5) O3 ceramic powder, BaTiO3 seed crystal template and modified nano silver particles are mixed in a mass ratio of 100:1-10:0.2-0.5 to obtain a mixed powder, a solvent and a dispersant are added, and the mixture is ball-milled for 4-12 hours, and then a plasticizer and a binder are added and the ball-milling is continued for 10-48 hours at a ball-milling speed of 240 r / min to obtain a matrix slurry;

[0008] The 1-x(Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5 ) The preparation method of O3 ceramic powder comprises the following steps:

[0009] TiO2, Bi2O3, Na2CO3, Al2O3, CaCO3 and Nb2O5 were dried at 100-120℃ for 3h and then prepared according to formula 1-x (Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5 )O3 (0≤x≤0.3) was weighed and mixed with anhydrous ethanol and zirconium oxide grinding balls at a weight ratio of 3:2:1 for 10-24 hours to obtain a slurry; after the slurry was dried, it was sieved and pressed into a blank, calcined at 800-1000°C for 2-3 hours, and then ball-milled again for 10-14 hours, and then dried and sieved with 80 mesh to obtain 1-x (Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5 )O3 ceramic powder; preferably, x is 0.12;

[0010] The preparation method of the BaTiO3 seed crystal template comprises the following steps:

[0011] S11. After mixing bismuth oxide and titanium dioxide in a molar ratio of 1:3-5, sodium chloride, potassium chloride and anhydrous ethanol were added, poured into a ball mill and fully ball-milled for 10-24 hours to obtain a slurry, dried at 60-80°C, pre-calcined at 1000°C for 2-3 hours, and ultrasonically cleaned with deionized water to remove the molten salt, and dried to obtain Bi4Ti3O 12 Precursor;

[0012] S12. Bi4Ti3O with a molar ratio of 1:3-5 12After the precursor and the BaCO3 dry raw material are mixed, molten salt NaCl or KCl of the same mass as the mixed material is added, anhydrous ethanol is added for ball milling for 8-12 hours, dried at 60-80°C, calcined at 740°C for 2-3 hours, stirred and washed three times with 3 mol / L dilute HNO3 to remove the reaction by-product Bi2O3, and then ultrasonically cleaned and dried with deionized water at 60-80°C to obtain a

[001] c oriented flaky BaTiO3 seed crystal template; the BaTiO3 template in the S12 has a length of 5-15 μm and a radial ratio of ≥10;

[0013] The preparation method of the modified nano silver particles comprises the following steps:

[0014] Disperse 1g of nanosilver in 100mL of toluene, stir magnetically for 10-30min, add PVP (polyvinyl pyrrolidone), the mass of PVP is 2% of the mass of nanosilver, heat to 50-90°C, stir magnetically for 9-12h, and the stirring speed is 180-220r / min; centrifuge, wash the precipitate with deionized water, and vacuum dry at 30-50°C to obtain modified nanosilver particles;

[0015] S2. Add cyclohexanone to the base slurry, stir for 0.5-2h under vacuum and 30-50°C, and stir at a speed of 60-300r / min to obtain a uniform slurry with bubbles removed; cast the uniform slurry into a film tape with a thickness of 50-80μm, and dry it at 50-90°C to form a thick film;

[0016] S3. Screen-printing nickel paste on the thick film as the inner electrode, stacking them layer by layer from bottom to top in the stacking mode of thick film-inner electrode-thick film, ensuring that the electrodes in adjacent film layers are staggered, until the stacking reaches a thickness of 2-10 mm, hot pressing to make the film fit tightly, and then cutting into 5 cm×8 cm block green film sheets;

[0017] S4. The green diaphragm is heated to 500-550°C for debinding, the heating rate is 3-5°C / min, and the holding time is 3-5h; then the temperature is raised to 1150-1200°C at a heating rate of 3-5°C / min, and then the temperature is lowered to 1080°C at a cooling rate of 10°C / min, and the temperature is kept for 8-10h to obtain a ceramic actuator block; the temperature reduction sintering can reduce the volatilization of the metal of the inner electrode;

[0018] S5. Silver electrodes are prepared by screen printing silver paste on the upper and lower surfaces and left and right sides of the ceramic actuator block. The left and right side silver electrodes are staggered and connected to the inner electrode. After silver is calcined at 850°C for 30 minutes, copper wires are welded on the upper and lower surfaces to obtain a piezoelectric brake.

[0019] S6. Polarize the piezoelectric brake under an electric field with a polarization electric field of 1-3 kV / cm, a temperature of 30-50°C, and a time of 10-30 min.

[0020] Furthermore, the purity of TiO2, Bi2O3, Na2CO3, Al2O3, CaCO3 and Nb2O5 is greater than 98%.

[0021] Furthermore, the molar ratio of sodium chloride to potassium chloride in S11 is 1:1.06.

[0022] Furthermore, the mass ratio of the mixed powder, solvent, dispersant, plasticizer and binder in S1 is 50:40:2:3:5.

[0023] Furthermore, the solvent in S1 is a mixed solution of 2-xylene and anhydrous ethanol in a mass ratio of 1:1.

[0024] Furthermore, the dispersant in S1 is triolein.

[0025] Furthermore, the plasticizer in S1 is a mixture of polyethylene glycol and dibutyl phthalate in a mass ratio of 1:1.

[0026] Furthermore, the binder in S1 is polyvinyl butyral.

[0027] Furthermore, the mass ratio of the matrix slurry to cyclohexanone in S2 is 50:1.

[0028] Furthermore, during the casting process in S2, the distance between the scraper and the casting base belt is set to 100-140 μm, and the scraper travel speed is 30-40 cm / min.

[0029] Furthermore, in S3, the hot pressing temperature is 60-80° C., the hot pressing pressure is 10-40 MPa, and the hot pressing time is 20-60 min.

[0030] An application of the piezoelectric actuator prepared by the above preparation method in piezoelectric power generation materials.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The invention discloses a preparation method and application of a textured ceramic / nanosilver particle composite laminated piezoelectric actuator. First, a

[001] c oriented barium titanate seed crystal is prepared, and a lead-free 1-x (Bi2O3) with a high orientation along

[001] c is prepared by using a template oriented growth technology. 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5)O3 textured ceramics; then prepare modified nanosilver particles, and finally prepare textured ceramic / nanosilver particle composite laminated piezoelectric actuators by tape casting. Directed growth texturing technology is used to keep the orientation of ceramic grains consistent, and doping with nanosilver particles improves electron mobility, thereby further improving output performance. The laminated structure can effectively reduce the driving voltage, increase the displacement, and effectively improve the piezoelectric performance. Finally, a high-strain, low-strain hysteresis strain loop is obtained. When the electric field is 30kV / cm, the displacement output reaches 0.65%; it can be widely used in piezoelectric power generation materials such as piezoelectric micro-displacement actuators and piezoelectric sensors with stable piezoelectric performance, high sensitivity, and high precision. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The present invention will be further described below in conjunction with the accompanying drawings.

[0034] Figure 1 is a cross-sectional schematic diagram of the structure of the textured ceramic / nanosilver particle composite laminated piezoelectric actuator in the present invention;

[0035] Figure 2 is a schematic diagram of the piezoelectric displacement of the piezoelectric actuator prepared in Example 4 of the present invention;

[0036] Figure 3 It is a schematic diagram of the piezoelectric displacement of the piezoelectric actuator obtained by preparing the structures of Examples 5-6 and Comparative Examples 1-2 of the present invention;

[0037] In the figure: 1. Inner electrode; 2. Copper wire; 3. Silver electrode; 4. Textured ceramic / nanosilver particle thick film. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] A method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator comprises the following steps:

[0040] S1.1-x(Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5)O3 ceramic powder, BaTiO3 seed crystal template and modified nano silver particles are mixed in a mass ratio of 100:1-10:0.2-0.5 to obtain a mixed powder, a solvent (a mixed solution of 2-xylene and anhydrous ethanol in a mass ratio of 1:1) and a dispersant (triolein) are added, and ball milling is performed for 4-12 hours, and then a plasticizer (a mixture of polyethylene glycol and dibutyl phthalate in a mass ratio of 1:1) and a binder (polyvinyl butyral) are added, and ball milling is continued for 10-48 hours, and the ball milling speed is 240r / min to obtain a matrix slurry; the mass ratio of the mixed powder, solvent, dispersant, plasticizer and binder is 50:40:2:3:5;

[0041] The 1-x(Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5 ) The preparation method of O3 ceramic powder comprises the following steps:

[0042] TiO2, Bi2O3, Na2CO3, Al2O3, CaCO3 and Nb2O5 with purity greater than 98% were dried at 100-120°C for 3 hours and then prepared according to formula 1-x (Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5 )O3 (0≤x≤0.3) is weighed (with an accuracy of 0.0001g) in a stoichiometric ratio, and ball-milled for 10-24h with anhydrous ethanol and zirconium oxide grinding balls in a weight ratio of 3:2:1 to obtain a slurry; after the slurry is dried, it is sieved and pressed into a blank, covered with an alumina crucible, calcined at 800-1000°C for 2-3h, and then ball-milled again for 10-14h, and after drying, it is sieved with an 80-mesh sieve to obtain a ceramic powder;

[0043] The preparation method of the BaTiO3 seed crystal template comprises the following steps:

[0044] S11. After mixing bismuth oxide and titanium dioxide in a molar ratio of 1:3-5, sodium chloride and potassium chloride in a molar ratio of 1:1.06 were added, and then anhydrous ethanol was added, poured into a ball mill and fully ball-milled for 10-24 hours to obtain a slurry, dried at 60-80°C, pre-calcined at 1000°C for 2-3 hours, and ultrasonically cleaned with deionized water to remove the molten salt, and dried to obtain Bi4Ti3O 12 Precursor;

[0045] S12. Bi4Ti3O with a molar ratio of 1:3-5 12After the precursor and the BaCO3 dry raw material are mixed, molten salt NaCl or KCl of the same mass as the mixed material is added, anhydrous ethanol is added for ball milling for 8-12 hours, dried at 60-80°C, calcined at 740°C for 2-3 hours, and washed with 3 mol / L dilute HNO3 for three times by stirring to remove the reaction by-product Bi2O3, and then ultrasonically cleaned and dried with deionized water at 60-80°C to obtain a

[001] c oriented flaky BaTiO3 seed crystal template; the BaTiO3 template has a length of 5-15μm and a radial ratio of ≥10.

[0046] The preparation method of the modified nano silver particles comprises the following steps:

[0047] Disperse 1g of nanosilver in 100mL of toluene, stir magnetically for 10-30min, add PVP, the mass of PVP is 2% of the mass of nanosilver, heat to 50-90°C, stir magnetically for 9-12h, and the stirring speed is 180-220r / min; centrifuge, wash the precipitate with deionized water, and vacuum dry at 30-50°C to obtain modified nanosilver particles;

[0048] S2. Add cyclohexanone to the matrix slurry (the mass ratio of slurry to cyclohexanone is 50:1), stir for 0.5-2h under vacuum and 30-50°C, and the stirring speed is 60-300r / min to obtain a uniform slurry with bubbles removed; cast the uniform slurry in a casting machine, set the distance between the scraper and the casting base tape to 100-140μm, and the scraper travel rate is 30-40cm / min. Finally, cast the uniform slurry into a film tape with a thickness of 50-80μm, and dry it at 50-90°C to form a thick film;

[0049] S3. Screen print nickel paste on the thick film as internal electrode, refer to Figure 1 , a cross-sectional schematic diagram of the structure of a textured ceramic / nanosilver particle composite laminated piezoelectric actuator (in the figure, 1 is an inner electrode; 2 is a copper wire; 3 is a silver electrode; 4 is a textured ceramic / nanosilver particle thick film); stacking layers from bottom to top, while ensuring that the electrodes in adjacent film layers are staggered, until the stacking reaches a thickness of 2-10 mm, hot pressing is performed by a hot press to make the film fit tightly, the hot pressing temperature is 60-80°C, the pressure is set to 10-40MPa, the hot pressing time is 20-60min, and then cut into 5cm×8cm block green film by a cutting machine;

[0050] S4. The green diaphragm is heated to 500-550°C for debinding, the heating rate is 3-5°C / min, and the holding time is 3-5h; then the temperature is increased to 1150-1200°C at a heating rate of 3-5°C / min, and then the temperature is decreased to 1080°C at a cooling rate of 10°C / min, and the temperature is kept for 8-10h to obtain a ceramic actuator block;

[0051] S5. Prepare silver electrodes by screen printing silver paste on the upper and lower surfaces and left and right sides of the ceramic actuator block, while ensuring that the left and right side silver electrodes are staggered and connected to the inner electrode, and after calcining the silver at 850°C for 30 minutes, weld copper wires on the upper and lower surfaces to obtain a piezoelectric brake;

[0052] S6. Polarize the piezoelectric brake under an electric field with a polarization electric field of 1-3 kV / cm, a temperature of 30-50°C, and a time of 10-30 min.

[0053] Example 1

[0054] 1-x(Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5 )O3, x=0.12 The preparation method of ceramic powder comprises the following steps:

[0055] (1) TiO2, Bi2O3, Na2CO3, Al2O3, CaCO3 and Nb2O5 with purity greater than 98% were placed in an oven at 110°C for 3 h to remove moisture and improve weighing accuracy. 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5 )O3, x = 0.12 stoichiometric ratio weighing, accuracy 0.0001g,

[0056] (2) Pour the prepared powder, anhydrous ethanol and zirconium oxide grinding balls into a ball mill in a weight ratio of 3:2:1 and mill for 18 hours to obtain a slurry;

[0057] (3) The slurry was placed in an oven to dry, sieved and pressed into a blank, covered with alumina and dried, and calcined at 900°C for 2.5 hours. The calcined blank was ball-milled again for 12 hours, dried and sieved with an 80-mesh sieve to obtain 0.88 (Bi 0.5 Na 0.5 )TiO3-0.12Ca(Al 0.5 Nb 0.5 )O3 ceramic powder.

[0058] In the following embodiments, 0.88 (Bi 0.5 Na 0.5 )TiO3-0.12Ca(Al 0.5 Nb 0.5 )O3 ceramic powders are all prepared by the preparation method described in this embodiment.

[0059] Example 2

[0060] The preparation method of the BaTiO3 seed crystal template comprises the following steps:

[0061] S11. After mixing bismuth oxide and titanium dioxide in a molar ratio of 1:4, sodium chloride and potassium chloride in a molar ratio of 1:1.06 were added, and then anhydrous ethanol was added, poured into a ball mill and fully ball-milled for 18 hours to obtain a slurry, dried at 70°C, pre-calcined at 1000°C for 2.5 hours, and ultrasonically cleaned with deionized water to remove the molten salt, and dried to obtain Bi4Ti3O 12 Precursor;

[0062] S12. Bi4Ti3O with a molar ratio of 1:4 12 After the precursor and the BaCO3 dry raw material are mixed, molten salt NaCl of the same mass as the mixed material is added, anhydrous ethanol is added for ball milling for 10 hours, dried at 70°C, calcined at 740°C for 2.5 hours, and washed three times with 3 mol / L dilute HNO3 to remove the reaction by-product Bi2O3, and then ultrasonically cleaned and dried with deionized water at 70°C to obtain a

[001] c oriented flaky BaTiO3 seed crystal template; the BaTiO3 template has a length of 10μm and a radial ratio ≥10.

[0063] The BaTiO3 seed crystal templates in the following examples are all prepared by the preparation method described in this example.

[0064] Example 3

[0065] The preparation method of modified nano silver particles comprises the following steps:

[0066] Disperse 1 g of nanosilver in 100 mL of toluene, stir magnetically for 20 min, add 0.02 g of PVP, heat to 75°C, stir magnetically for 10.5 h, and stir at a speed of 200 r / min; centrifuge, wash the precipitate with deionized water, and dry in vacuum at 40°C to obtain modified nanosilver particles.

[0067] The modified nanosilver particles in the following examples are all prepared by the preparation method described in this example.

[0068] Example 4

[0069] A method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator comprises the following steps:

[0070] S1.0.88(Bi 0.5 Na 0.5 )TiO3-0.12Ca(Al 0.5 Nb 0.5)O3 ceramic powder, BaTiO3 seed crystal template and modified nano silver particles are mixed in a mass ratio of 100:5:0.35 to obtain a mixed powder, a solvent (a mixed solution of 2-xylene and anhydrous ethanol in a mass ratio of 1:1) and a dispersant (triolein) are added, and after ball milling for 8 hours, a plasticizer (a mixture of polyethylene glycol and dibutyl phthalate in a mass ratio of 1:1) and a binder (polyvinyl butyral) are added, and ball milling is continued for 30 hours at a ball milling speed of 240 r / min to obtain a matrix slurry; the mass ratio of the mixed powder, solvent, dispersant, plasticizer and binder is 50:40:2:3:5;

[0071] S2. Add cyclohexanone to the matrix slurry (the mass ratio of the matrix slurry to cyclohexanone is 50:1), stir for 1.2 h under vacuum and 40°C, and the stirring speed is 200 r / min to obtain a uniform slurry with bubbles removed; cast the uniform slurry in a casting machine, set the distance between the scraper and the casting base tape to 120 μm, and the scraper travel rate is 35 cm / min. Finally, cast the uniform slurry into a film tape with a thickness of 65 μm, and dry it at 70°C to form a thick film;

[0072] S3. Screen print nickel paste on the thick film as internal electrode, refer to Figure 1 , stacked layer by layer from bottom to top, while ensuring the staggered distribution of electrodes in adjacent membrane layers, until the stacking reaches a thickness of 5 mm, hot pressing is performed by a hot press to make the membrane fit tightly, the hot pressing temperature is 70°C, the pressure is set to 25MPa, the hot pressing time is 40min, and then cut into 5cm×8cm block green membrane sheets by a cutting machine;

[0073] S4. The green diaphragm was heated to 530°C for debinding, with a heating rate of 4°C / min and a holding time of 4h; then the temperature was raised to 1175°C at a heating rate of 4°C / min, and then the temperature was lowered to 1080°C at a cooling rate of 10°C / min, and the temperature was kept for 9h to obtain a ceramic actuator block;

[0074] S5. Prepare silver electrodes by screen printing silver paste on the upper and lower surfaces and left and right sides of the ceramic actuator block, while ensuring that the left and right side silver electrodes are staggered and connected to the inner electrode, and after calcining the silver at 850°C for 30 minutes, weld copper wires on the upper and lower surfaces to obtain a piezoelectric brake;

[0075] S6. Polarize the piezoelectric actuator under an electric field with a polarization electric field of 1.5 kV / cm, a temperature of 40°C, and a time of 20 min.

[0076] Example 5

[0077] A method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator comprises the following steps:

[0078] S1.0.88(Bi 0.5 Na 0.5 )TiO3-0.12Ca(Al 0.5 Nb 0.5 )O3 ceramic powder, BaTiO3 seed crystal template and modified nano silver particles are mixed in a mass ratio of 100:2:0.35 to obtain a mixed powder, a solvent (a mixed solution of 2-xylene and anhydrous ethanol in a mass ratio of 1:1) and a dispersant (triolein) are added, and after ball milling for 8 hours, a plasticizer (a mixture of polyethylene glycol and dibutyl phthalate in a mass ratio of 1:1) and a binder (polyvinyl butyral) are added, and ball milling is continued for 30 hours at a ball milling speed of 240 r / min to obtain a matrix slurry; the mass ratio of the mixed powder, solvent, dispersant, plasticizer and binder is 50:40:2:3:5;

[0079] S2, S3, S4, S5 and S6 are the same as those in Example 4.

[0080] Example 6

[0081] A method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator comprises the following steps:

[0082] S1.0.88(Bi 0.5 Na 0.5 )TiO3-0.12Ca(Al 0.5 Nb 0.5 )O3 ceramic powder, BaTiO3 seed crystal template and modified nano silver particles are mixed in a mass ratio of 100:10:0.35 to obtain a mixed powder, a solvent (a mixed solution of 2-xylene and anhydrous ethanol in a mass ratio of 1:1) and a dispersant (triolein) are added, and after ball milling for 8 hours, a plasticizer (a mixture of polyethylene glycol and dibutyl phthalate in a mass ratio of 1:1) and a binder (polyvinyl butyral) are added, and ball milling is continued for 30 hours at a ball milling speed of 240 r / min to obtain a matrix slurry; the mass ratio of the mixed powder, solvent, dispersant, plasticizer and binder is 50:40:2:3:5;

[0083] S2, S3, S4, S5 and S6 are the same as those in Example 4.

[0084] Comparative Example 1

[0085] A method for preparing a composite laminated piezoelectric actuator comprises the following steps:

[0086] S1.0.88(Bi 0.5 Na 0.5 )TiO3-0.12Ca(Al 0.5 Nb 0.5)O3 ceramic powder, BaTiO3 seed crystal template and modified nano silver particles are mixed in a mass ratio of 100:0:0.35 to obtain a mixed powder, a solvent (a mixed solution of 2-xylene and anhydrous ethanol in a mass ratio of 1:1) and a dispersant (triolein) are added, and after ball milling for 8 hours, a plasticizer (a mixture of polyethylene glycol and dibutyl phthalate in a mass ratio of 1:1) and a binder (polyvinyl butyral) are added, and ball milling is continued for 30 hours at a ball milling speed of 240r / min to obtain a matrix slurry; the mass ratio of the mixed powder, solvent, dispersant, plasticizer and binder is 50:40:2:3:5;

[0087] S2, S3, S4, S5 and S6 are the same as those in Example 4.

[0088] Comparative Example 2

[0089] A method for preparing a composite laminated piezoelectric actuator comprises the following steps:

[0090] S1.0.88(Bi 0.5 Na 0.5 )TiO3-0.12Ca(Al 0.5 Nb 0.5 )O3 ceramic powder and BaTiO3 seed crystal template are mixed in a mass ratio of 100:5 to obtain a mixed powder, a solvent (a mixed solution of 2-xylene and anhydrous ethanol in a mass ratio of 1:1) and a dispersant (triolein) are added, and after ball milling for 8 hours, a plasticizer (a mixture of polyethylene glycol and dibutyl phthalate in a mass ratio of 1:1) and a binder (polyvinyl butyral) are added, and ball milling is continued for 30 hours at a ball milling speed of 240r / min to obtain a matrix slurry; the mass ratio of the mixed powder, solvent, dispersant, plasticizer and binder is 50:40:2:3:5;

[0091] S2, S3, S4, S5 and S6 are the same as those in Example 4.

[0092] The piezoelectric performance of Examples 4 to 6 and Comparative Examples 1 to 2 was tested, and the test results are shown in Table 1:

[0093] Table 1

[0094] Implementation Cases Texture <![CDATA[d 33 (pc / N)]]> Example 4 95.60% 830 Example 5 86.20% 420 Example 6 99.30% 710 Comparative Example 1 0% 210 Comparative Example 2 95.10% 700

[0095] From Table 1, we can see that 0.88(Bi 0.5 Na 0.5 )TiO3-0.12Ca(Al 0.5 Nb 0.5 )O3 ceramic powder and BaTiO3 seed crystal template mass ratio is 100:5, the piezoelectric coefficient (d 33 ) reaches a maximum value of 830pc / N; 0.88(Bi0.5 Na 0.5 )TiO3-0.12Ca(Al 0.5 Nb 0.5 ) When the mass ratio of BaTiO3 ceramic powder to BaTiO3 seed crystal template is 100:10, the piezoelectric coefficient drops to 710pc / N, indicating that the more BaTiO3 seed crystal template content, the better;

[0096] The piezoelectric displacement of Examples 4 to 6 and Comparative Examples 1 to 2 was tested. Under the condition of an electric field strength of 3 kV / cm, the displacement output of the piezoelectric actuator prepared in Example 4 was as follows: Figure 2 As shown, it reaches 0.65%; the displacement output of the piezoelectric actuators prepared in Example 5-Example 6 and Comparative Example 1-Comparative Example 2 under the same electric field of 3kV / cm is as shown Figure 3 As shown;

[0097] According to Table 1 and Figure 3 When modified nanosilver particles are not added to the mixed powder, the performance of the prepared piezoelectric actuator is worse than that of the piezoelectric actuator prepared by adding modified nanosilver particles under the same conditions. This is because doping with modified nanosilver particles is beneficial to improving electron mobility, thereby further improving output performance.

[0098] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator, characterized in that: The steps include: S1.1-x(Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5 )O3, 0≤x≤0.3 ceramic powder, BaTiO3 The seed crystal template and the modified nano silver particles are mixed in a mass ratio of 100:1-10:0.2-0.5 to obtain a mixed powder, a solvent and a dispersant are added, and after mixing, a plasticizer and a binder are added to prepare a matrix slurry; the mass ratio of the mixed powder, the solvent, the dispersant, the plasticizer and the binder is 50:40:2:3:5; the BaTiO3 seed crystal template has a length of 5-15 μm and a radial ratio of ≥10; S2. Add cyclohexanone to the base slurry, stir for 0.5-2h under vacuum and 30-50°C, and stir at a speed of 60-300r / min to obtain a uniform slurry with bubbles removed; cast the uniform slurry into a film tape with a thickness of 50-80μm, and dry it at 50-90°C to form a thick film; S3. Screen-printing nickel paste on the thick film as the inner electrode, stacking them layer by layer from bottom to top in the stacking mode of thick film-inner electrode-thick film, with the inner electrodes of adjacent film layers staggered until the stacking reaches a thickness of 2-10 mm, hot pressing to make the film fit tightly, and then cutting into 5 cm×8 cm block green film sheets; S4. The green diaphragm is heated to 500-550°C for debinding, the heating rate is 3-5°C / min, and the holding time is 3-5h; then the temperature is increased to 1150-1200°C at a heating rate of 3-5°C / min, and then the temperature is decreased to 1080°C at a cooling rate of 10°C / min, and the temperature is kept for 8-10h to obtain a ceramic actuator block; S5. Silver electrodes are prepared by screen printing silver paste on the upper and lower surfaces and left and right sides of the ceramic actuator block. The left and right side silver electrodes are staggered and connected to the inner electrode. After silver is calcined at 850°C for 30 minutes, copper wires are welded on the upper and lower surfaces to obtain a piezoelectric brake. S6. Polarize the piezoelectric brake under an electric field with a polarization electric field of 1-3 kV / cm, a temperature of 30-50°C, and a time of 10-30 min.

2. The method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator according to claim 1, characterized in that: The preparation method of the BaTiO3 seed crystal template in S1 comprises the following steps: S11. After mixing bismuth oxide and titanium dioxide in a molar ratio of 1:3-5, sodium chloride, potassium chloride and anhydrous ethanol were added, and the mixture was ball-milled for 10-24 hours to obtain a slurry, dried at 60-80°C, pre-calcined at 1000°C for 2-3 hours, ultrasonically cleaned with deionized water, and dried to obtain Bi4Ti3O 12 Precursor; S12. Bi4Ti3O with a molar ratio of 1:3-5 12 After the precursor and the BaCO3 dry raw material are mixed, add molten salt NaCl or KCl of the same mass as the mixed material, add anhydrous ethanol and ball mill for 8-12 hours, dry at 60-80°C, place at 740°C for 2-3 hours, and wash and dry with 3 mol / L dilute HNO3 and 60-80°C deionized water in turn to obtain a BaTi O3 seed crystal template.

3. The method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator according to claim 2, characterized in that: The molar ratio of sodium chloride to potassium chloride in S11 is 1:1.

06.

4. The method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator according to claim 1, characterized in that: The S1 1-x (Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5 )O3, 0≤x≤0.3 The preparation method of ceramic powder comprises the following steps: After drying, TiO2, Bi2O3, Na2CO3, Al2O3, CaCO3 and Nb2O5 were quantified according to 1-x (Bi 0.5 Na 0.5 )TiO3-xCa(Al 0.5 Nb 0.5 )O3, 0≤x≤0.3 in a stoichiometric ratio, and ball-milled for 10-24 hours with anhydrous ethanol and zirconium oxide grinding balls in a weight ratio of 3:2:1 to obtain a slurry; after the slurry is dried, it is sieved and pressed into a blank, calcined at 800-1000°C for 2-3h, and then ball-milled again for 10-14h, and after drying, it is sieved through an 80-mesh sieve to obtain a ceramic powder.

5. The method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator according to claim 1, characterized in that: The method for preparing the modified nano silver particles in S1 comprises the following steps: Nanosilver is added to toluene and dispersed for 10-30 minutes, then PVP is added, and the mixture is heated to 50-90°C and reacted for 9-12 hours; the mixture is centrifuged, washed with deionized water, and vacuum dried at 30-50°C to obtain modified nanosilver particles; the dosage ratio of the nanosilver, toluene and PVP is 1g:100mL:0.02g.

6. The method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator according to claim 1, characterized in that: The solvent in S1 is a mixed solution of 2-xylene and anhydrous ethanol in a mass ratio of 1:1; The dispersant is triolein; the plasticizer is a mixture of polyethylene glycol and dibutyl phthalate in a mass ratio of 1:1; and the binder is polyvinyl butyral.

7. The method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator according to claim 1, characterized in that: The mass ratio of the matrix slurry to cyclohexanone in S2 is 50:

1.

8. The method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator according to claim 1, characterized in that: During the casting process in S2, the distance between the scraper and the casting base belt is set to 100-140 μm, and the moving speed of the scraper is 30-40 cm / min.

9. The method for preparing a textured ceramic / nanosilver particle composite laminated piezoelectric actuator according to claim 1, characterized in that: In the S3, the hot pressing temperature is 60-80° C., the hot pressing pressure is 10-40 MPa, and the hot pressing time is 20-60 min.

10. Application of the piezoelectric actuator prepared by the preparation method according to any one of claims 1 to 9 in piezoelectric power generation materials.